Sorting and wage premiums in immoral work - Florian H. Schneider; Fanny Brun; Roberto A. Weber (University of Zurich, Department of Economics, 2020)
We use surveys, laboratory experiments and administrative labor-market data to study how heterogeneity in the perceived immorality of work and in workers' aversion to acting immorally interact to impact labor market outcomes. Specifically, we investigate whether those individuals least concerned with acting morally select into jobs generally perceived as immoral and whether the aversion among many individuals to performing such acts contributes to immorality wage premiums, a form of compensating differential. We show that immoral work is associated with higher wages, both using correlational evidence from administrative labor-market data and causal evidence from a laboratory experiment. We also measure individuals' aversion to performing immoral acts and show that those who find immoral behavior least aversive are more likely to be employed in immoral work in the lab and have a relative preference for work perceived as immoral outside the laboratory. We note that sorting by "immoral" types into jobs that can cause harm may be detrimental for society. Our study highlights the value of employing complementary research methods.
Keywords: C92; J31; D03; 330; wage premium; immoral behavior; sorting; experiments